Existence of solution for a mixed neutral system. (1992) - Balachandran, K.; Anguraj, A.
Abstract : We prove the existence of unique solution of the mixed neutral system x ′ ( t ) = f ( t, x ) + ∑ j = 1 m A j ( t, x ) x ′ ( t + p j ) + g ( t, x, x ′ ( t + h ) ) x ( 0 ) = x 0 and also prove the continuous dependence of the solution.